't Aksent. - Aksent op Roze (Gent : AOR, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Postbus 434, 9000 Gent
Zie Gebundeld Zweet voor de zomernummers van de jaren 1996-2000
Nederlands
Periodiek